Obtenção, modificação e utilização de nanocristais de celulose - Spagnol, Cristiane (2013)
In this paper cellulose nanocrystals were prepared from cotton fibers by hydrolysis with hydrochloric acid. The surface of the nanocrystals cellulose was modified with maleic anhydride, succinic, phthalic and acetic. The nanocrystals of cellulose and modified cellulose nanocrystals were characterized by MET, AFM, FTIR, 13C NMR, XRD and TGA. By means of acid hydrolysis cotton was possible to obtain nanocrystals aspect ratio (L/D) of about 9?3. The surface modification of the nanocrystals with the use of anhydrides has been obtained by a simple route, thus obtaining modified biopolymers with average degree of substitution of 1.22 that have good dispersion in polar solvents. Cellulose nanocrystals and modified cellulose nanocrystals anhydrides were added at a ratio of 3, 6 and 9% poly(vinyl alcohol) with different degrees of hydrolysis (88% and 98% hydrolyzed) plasticized with glycerol, obtaining films by casting, which were characterized by XRD, TGA, DMA, and mechanical testing. The addition of the modified cellulose nanocrystals PVA98 generating an increase in thermal degradation of the composite film. The results of the mechanical tests show that the addition of nanocrystals modified nanocrystals and changes the values of tensile strength, modulus and elongation at break and elasticity of the films with respect to PVA films without the addition of biopolymers. The largest increases in tensile strength were obtained for the films using PVA98, indicating that the biopolymers has great potential application in enhancing polymer PVA. Were also incorporated silver nanoparticles on cellulose nanocrystals modified with succinic anhydride which served as sites for anchoring and stabilizing the formation of silver nanoparticles, the material produced was characterized by MET, SEM, EDX, TGA, XRD and submitted for assessment antimicrobial activity against Staphylococcus aureus, Escherichia coli, Bacillus subtilis and Candida albicans, and the results obtained demonstrate great potential for use of silver nanoparticles embedded in cellulose nanocrystals modified. The nanoparticles incorporated into the nanocrystals were used to produce nanocomposites films obtained with casting and PVA electrospinning, through microbiological testing showed that the films formed halos generated growth inhibition, demonstrating the antimicrobial activity of films. Also incorporated in the nanoparticles nanocrystals were used to produce nanocomposites films with PNIPAAm, it was found that by microbiological assays inhibition generated halos were lower than those obtained for the PVA film, which carries a lower antimicrobial activity of films containing the PNIPAAm silver nanoparticles